EXPLORING COX-1 AND COX-2 INHIBITION POTENTIAL OF AMBERBOA DIVARICATA AERIAL PARTS THROUGH IN-SILICO AND IN-VITRO STUDIES - Dr. Prasad Mettikolla; Dr. T. Sunil Kumar Reddy; Dr. G. Balammal (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Acute and chronic inflammatory illnesses continue to be one of the world’s most serious public health issues. Although various medications are known to treat inflammatory illnesses, long-term treatment frequently results in severe side effects. This study aimed to identify the COX-1 and COX-2 inhibitory potential of Amberboa divaricata through in-silico and in-vitro studies. The extract was prepared using the ether:petroleum ether (1:2) and dried to obtain the residue which was further used for the assay. The assay was performed using the kit and the ligands (phytoconstituents) were docked against the COX-1 and COX-2 by docking studies. The assay showed an inhibition rate of 61.32% COX-2 and 59.01% (COX-1) at 100 µg/ml. The IC50 of the extract residue was 75.10 µg/ml (COX-1) and 70.76 µg/ml (COX-2). The docking studies revealed that only cynaropicrin and desacylcynaropicrin interacted with the active sites of the COX-1 and COX-2 owing to the hydrophilic binding nature of the proteins. Further isolation and preclinical studies is needed to identify the complete potential of the phytoconstituents and their effect on COX-1 and COX-2 targets.